Implementasi teori belajar behavioristik dalam pendidikan Islam anak usia dini - Nurselly, Tania Tiara (Maliki Interdisciplinary Journal, 2024)
Age is the first period that will be passed by every individual in living life in the world. At this time children quickly experience growth and development such as psychic, physiological, motor, cognitive, language and other developments. In this stage of development can be used as a basis for how in the future children will develop. Children at an early age often have difficulty in adjusting so a behavioral approach is needed. The behavioral science approach is a theory of the development and change of behavior that is measured, observed, and induced by the environment, so as to produce responses during the process of adaptation to the environment in early childhood. Detailed application of the theory of behaviorist approaches to motivations, attitudes, and interests.